JNSR 2019
DOI: 10.7176/jnsr/9-6-04
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Harvest Index in Improving Crop Productivity: A Review

Abstract: Harvest index (HI) is a measure of success in partitioning assimilated photosynthate. An improvement of crop harvest index means an increase in the economic portion of the crops in certain level. HI is a novel trait which contributed significant role in improvement of crop productivity which could solve the problem of food supplies for the rapidly increasing population. The objective of this paper was to review the role and progress of HI in improving crop productivity. Although crop HI influenced by both envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…In cereals, HI values between 0.3 and 0.6 predominate [85][86][87][88]. The HI value can be modified by crop management [89]. Our experience has confirmed that agrotechnical treatments, such as foliar spraying with microelements, influence the increase in HI.…”
Section: Influence Of Experimental Factorssupporting
confidence: 62%
“…In cereals, HI values between 0.3 and 0.6 predominate [85][86][87][88]. The HI value can be modified by crop management [89]. Our experience has confirmed that agrotechnical treatments, such as foliar spraying with microelements, influence the increase in HI.…”
Section: Influence Of Experimental Factorssupporting
confidence: 62%
“…Harvest index (HI) is a way to measure how photosynthate splits up. When the crop harvest index goes up, it means that the crops' economic value goes to a certain amount (Asefa, 2019). Dry stem weight changes were linked to HI variations, and late sowing increased HI (Kawasaki et al, 2018).…”
Section: Yield Associated Traitsmentioning
confidence: 99%
“…The harvest index (HI) measures success in partitioning the results of photosynthate assimilation. An increase in the crop harvest index means an increase in the economic portion of the crop at a certain level [29]. A single effect of nitrogen fertilization (N) and irrigation markedly affected the average crop index (Table 3).…”
Section: Harvest Indexmentioning
confidence: 99%